Intangible assets and economical-financial performance: comparison between portfolios of tangible-intensive and intangible-intensive firms - Oliveira, Marta Olivia Rovedder de; Schossler, Douglas Pinheiro; Campus, Rogério Estrela; Luce, Fernando Bins (Revista de Administração da UFSM, 2014)
The intangible assets are able to produce future benefits that are important differentiating factors contributing to the achievement of important competitive advantages (CARMELI; TISHLER, 2004; PEREZ; FAMÁ, 2006a). However, traditional approaches to financial evaluation have difficulty in assessing and valuing business with significant intangible assets (LEV, 2001; MIZIK; JACOBSON, 2008; MIZIK; JACOBSON, 2009). Hence, this study sought to compare (by accountancy and financial indexes, during 5 years) the performance of two portfolios: firms with a high proportion of intangibility and one of possessing a small proportion of intangibility, in order to contribute to the literature and generate knowledge about the Brazilian market. The results show a superior performance of the intangible assets portfolio during the most of periods and indexes. It is further evidence that intangible assets are capable of generating competitive advantage for their respective companies, including in the Brazilian scenario.